2007
DOI: 10.1007/s00705-007-1051-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential for the replication of the betanodavirus redspotted grouper nervous necrosis virus in human cell lines

Abstract: The determination of the host ranges of viruses is important because of the possible emergence of infectious agents, which may result from the zoonotic transmission of animal viruses to humans. The family Nodaviridae, whose members are non-enveloped, positive-stranded bipartite RNA viruses, is comprised of the genera Alphanodavirus and Betanodavirus, whose members predominantly infect insects and fish, respectively. The alphanodaviruses can also infect suckling mice and suckling hamsters, resulting in paralysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…In order to investigate RNase activity, we extracted genome RNAs from influenza virus and Noda virus in accordance with past studies (17, 18). However, we failed to prepare influenza virus RNA because it was very unstable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate RNase activity, we extracted genome RNAs from influenza virus and Noda virus in accordance with past studies (17, 18). However, we failed to prepare influenza virus RNA because it was very unstable.…”
Section: Resultsmentioning
confidence: 99%
“…Genome RNAs from influenza virus and Noda virus were prepared in accordance with past studies (17, 18). Briefly, virions were recovered from the banding fraction by ultracentrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…The species of the first genus were originally isolated from insects (Fig. 1), but appear to infect both vertebrates and invertebrates, and to cause the death of insect and mammalian hosts (Adachi et al 2008). Betanodaviruses usually affect the nervous system of marine fish, leading to behavioural abnormalities and extreme high mortalities (Munday, Kwang & Moody 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The virus may also simply be trapped in the punctate structures described above. When studying RGNNV infection in human cell cultures, Adachi et al (2008) [10] showed that circumventing some obstacles early in the infection process may lead to the production of progeny RGNNV.…”
Section: Discussionmentioning
confidence: 99%
“…The fish virus betanodavirus Red grouper nervous necrosis virus (RGNNV) was shown to bind to human cells in cell culture, but was unable to enter into these cells. However, virus replication could be initiated by transfection of cells with viral RNA [10]. …”
Section: Introductionmentioning
confidence: 99%